Pupillary Response to Postural Demand in Parkinson’s Disease - Kahya, Melike; Lyons, Kelly E.; Pahwa, Rajesh; Akinwuntan, Abiodun E.; He, Jianghua; Devos, Hannes (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Individuals with Parkinson’s disease (PD) may need to spend more mental and physical effort (i.e., cognitive workload) to maintain postural control. Pupillary response reflects cognitive workload during postural control tasks in healthy controls but has not been investigated as a measure of postural demand in PD. Objectives: To compare pupillary response during increased postural demand using vision occlusion and dual tasking between individuals with PD and healthy controls. Methods: Thirty-three individuals with PD and 35 healthy controls were recruited. The four conditions lasted 60 seconds and involved single balance task with eyes open; single balance task with eyes occluded; dual task with eyes open; dual task with eyes occluded. The dual task comprised the Auditory Stroop test. Pupillary response was recorded using an eye tracker. The balance was assessed by using a force plate. Two-way Repeated Measures ANOVA and LSD post-hoc tests were employed to compare pupillary response and Center of Pressure (CoP) displacement across the four conditions and between individuals with PD and healthy controls. Results: Pupillary response was higher in individuals with PD compared to healthy controls (p=0.009) and increased with more challenging postural conditions in both groups (p<0.001). The post-hoc analysis demonstrated increased pupillary response in the single balance eyes occluded (p<0.001), dual task eyes open (p= 0.01), and dual task eyes occluded (p<0.001) conditions compared to single task eyes open condition. Conclusions: Overall, the PD group had increased pupillary response with increased postural demand compared to the healthy controls. In the future, pupillary response can be a potential tool to understand the neurophysiological underpinnings of falls risk in the PD population.